Investigation of Fretting Wear of Cladding Materials in Liquid Lead - Del Giacco, Mattia (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2013)
One promising concept for future nuclear reactors uses liquid metals like Pb as reactor coolant. In this work, fretting of fuel clad materials is investigated in Pb environment at relevant operating conditions. A novel test apparatus is presented that allows fretting tests in liquid lead with high accuracy and reproducibility also during long term tests. Tolerable operating conditions concerning fretting wear by evaluating the specific wear coefficient and the concept of fretting maps are given.